Bioprospection of single and a consortium endophytic bacteria of suboptimal field rice isolates as biocontrol of rice bacterial leaf blight pathogens - HERU ADI DJATMIKO; NUR PRIHATININGSIH; PUJI LESTARI (Society for Indonesian Biodiversity, 2023)
Abstract. Djatmiko HA, Prihatiningsih N, Lestari P. 2023. Bioprospection of single and a consortium endophytic bacteria of suboptimal field rice isolates as biocontrol of rice bacterial leaf blight pathogens. Biodiversitas 24: 2710-2715. Rice root endophytic bacteria isolated from suboptimal land have the potential to control leaf blight by Xanthomonas oryzae pv. oryzae (Xoo). The aim of this research was: 1) to test the potential of single and consortium endophytic bacteria single and consortium to control Xoo in vitro, 2) to know the antibiosis mechanism of this endophytic bacteria and 3) to evaluate the biochemical character of the single endophytic bacteria as an antagonist feature. The completely randomized design with 5 single and 1 consortium treatment, 4 replications was used as a research method. The inhibition was carried out using a diffusion method of 108 cfu/mL endophytic bacterial suspension. Filter paper 6 mm diameter had been dripped 10 µL suspension of endophytic bacteria, then it placed 3 spots on NA that had been poured with Xoo. The variable observed was the inhibition zone of endophytic bacteria, the inhibition mechanism, and the character as antagonist produces protease; and siderophore. The results showed that both single and consortium endophytic bacteria could potentially suppress Xoo in-vitro, and the best inhibition was the consortium with an inhibitory area of ??62.74 mm2 and the bacteriostatic mechanism. The consortium's antibiosis index was 1.49, it can produce protease and siderophore with clear zone and orange color features. The endophytic bacteria consortium has the potential as a biopesticide to be developed as an alternative to control rice bacterial leaf blight.